PERAN KOMITMEN ORGANISASI DALAM MEMEDIASI PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI - Muhammad Muchzamil; Sujono Sujono; Asrip Putera (Pascasarjana Universitas Halu Oleo, 2019)
This research inteds: 1) to examine the effect of work discipline on the commitment of Wakatobi Regency OPD organization, 2) to examine the effect of work discipline on the performance of Wakatobi Regency OPD employees, 3) to examine the effect of organization commitment on the performance of Wakatobi Regency OPD employees 4) to examine the role of organization commitment in mediating work discipline on the performance of Wakatobi Regency OPD employeesThe research subject of is the Regional Government Organization of Wakatobi Regency, the population of this research is all the employees who served as section heads in the Wakatobi Regency OPD which amounted 128 people. The size of the sample was determined with census technique, the study sample was 128 people. The data in the research were analyzed using path analysis with the help of smartPLS 2.0 software.Thesis: 1) work discipline has positive and significant effect on organization commitment, 2) work discipline has positive and significant effect on employees performance, 3) organizational commitment has positive and significant effects on employees performance, 4) organization commitment is able to mediate work discipline on employees performance.Keywords: work discipline, organization commitment and employees performance